Fluorescent AIE-Active Materials for Two-Photon Bioimaging Applications - Lu, Qing; Wu, Cheng-Juan; Liu, Zhiqiang; Niu, Guangle; Yu, Xiaoqiang (Frontiers in Chemistry, 2020)
Fluorescence imaging has been widely used as a powerful tool for in situ and real-time visualization of important analytes and biological events in live samples with remarkably high selectivity, sensitivity, and spatial resolution. Compared with one-photon fluorescence imaging, two-photon fluorescence imaging exhibits predominant advantages of minimal photodamage to samples, deep tissue penetration, and outstanding resolution. Recently, the aggregation-induced emission (AIE) materials have become a preferred choice in two-photon fluorescence biological imaging because of its unique bright fluorescence in solid and aggregate state and strong resistance to photobleaching. In this review, we will exclusively summarize the applications of AIE-active materials in two-photon fluorescence imaging with some representative examples from four aspects: fluorescence detection, in vitro cell imaging, ex vivo tissue imaging and in vivo vascular imaging. In addition, the current challenge and future development direction of AIE-active materials for two-photon bioimaging is also briefly discussed.